1993
DOI: 10.1002/cne.903350208
|View full text |Cite
|
Sign up to set email alerts
|

Giant terminals in the dorsal octavolateralis nucleus of lampreys

Abstract: The dorsal octavolateralis nucleus of lampreys is a primary nucleus for electroreceptive stimuli in the medulla. In Lampetra japonica, the rostral and caudal thirds of this nucleus are exclusively occupied by giant terminals, which become evident when the primary fibers of an electrosensory nerve (recurrent branch of the anterior lateral line nerve) are labeled with horseradish peroxidase. We studied the ultrastructure of these terminals. They contain neurofilaments, mitochondria, microtubules, and tubular mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…This notion is consistent with the absence of the mesencephalic trigeminal nucleus in the adult lamprey (reviewed by Sarnat and Netzky, 1981). The dorsal medullar neurons that have been suggested to be homologous with the gnathostome mesencephalic trigeminal nucleus (Northcutt, 1979; but see Finger andRovainen, 1982, andKoyama et al, 1987) were not found at any developmental stages observed by the methods used in the present study.…”
Section: Discussioncontrasting
confidence: 58%
“…This notion is consistent with the absence of the mesencephalic trigeminal nucleus in the adult lamprey (reviewed by Sarnat and Netzky, 1981). The dorsal medullar neurons that have been suggested to be homologous with the gnathostome mesencephalic trigeminal nucleus (Northcutt, 1979; but see Finger andRovainen, 1982, andKoyama et al, 1987) were not found at any developmental stages observed by the methods used in the present study.…”
Section: Discussioncontrasting
confidence: 58%
“…A and A–D; Ronan and Northcutt, ; Koyama et al, ; González and Anadón, ). Both anterior and posterior lateral line fibers bear numerous varicosities along their longitudinal extend; actually, giant nerve terminals were found at the rostral and caudal ends of the electroreceptive fibers in the dorsal nucleus of the octavolateral area (Kishida et al, ; Koyama et al, ). Electrophysiological recordings in the posterior lateral line nerve of larval and adult lampreys indicate the presence of mechanoreceptive fibers responding to water movements relative to the skin (Rovainen, ; Akoev and Muraveiko, ; Gelman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ampulla-shaped electroreceptor organs containing hair cells with cilia that can be excited by cathodal stimulation is a characteristic of crown gnathostomes (Fig. 1; Andres and von During 1988;Koyama et al 1993;Northcutt and Bleckmann 1993;Gibbs 2004). Electroreception is absent in living myxinoids (hagfishes), however lampreys have nonampullary electrosensory organs (Ronan and Bodznick 1986).…”
Section: Introductionmentioning
confidence: 99%
“…This sense has been lost in most amniotes and neopterygians, and may have re-evolved twice in teleosts (Fig. 1;Bullock 1982;Bullock et al 1983;Koyama et al 1993;Gibbs 2004). Chondrichthyans are the most basal lineage of crown gnathostomes to develop a highly specialized network of ampullary organs, known as the ampullae of Lorenzini.…”
Section: Introductionmentioning
confidence: 99%